Evaluation of Toxic Potentiality of Carbon Black on Respiratory Tract of Rats - Mounica, B.; Ch. Malathi Suvarna, B. Santosh Kumar (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Particle pollution is a threat to human health, especially Nanoparticle pollution is threatening. In the present study we are studying the toxicity of CARBON BLACK to assess their potential in damaging human health. Since carbon is an inhalational component of our everyday lives. Method: Rats are exposed to CARBON BLACK by inhalation and several parameters like haemoglobin%, RBC, WBC and Platelet Count, biochemical and hystopathological studies of exposed lung in comparison with blank. Results: Lung weights of rats exposed to carbon black were a little higher than the control group due to accumulation of lung fluid. It also showed an increase in WBC, RBC and Platelet count. 21 days after inhalation an acute neutrophil influx into the airspaces, with accompanying increased epithelial permeability. The lungs of the rats exhibited histological changes consistent with an inflammatory response, particle retention, and penetration of particles into the deep lung at the highest doses. Conclusion: The results obtained in the present study indicated that the carbon black particles of PM2.5 was retained in regions of the lungs, suggesting possible physical interaction of particles with surrounding cells and tissue and causes potential lung injury.